Influence of diet lysine level on performance of finishing barrows and gilts - K C Ferrell; G L Allee; B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1973)
One hundred eighteen barrows and gilts were used to evaluate adding lysine to a 11.2% crude protein, milo-soybean meal ration. Rate of gain was significantly improved (P<.05) in both barrows and gilts receiving the higher dietary levels of lysine, but not feed efficiency. Loin-eye area of barrows receiving three levels of lysine was not affected, but loin-eye area of gilts was significantly improved by the addition of lysine to the diet. Carcass length, backfat thickness and ham and loin percentage were not improved in either barrows or gilts. Rate of gain, feed efficiency, and carcass parameters did not differ significantly for pigs fed .65 or .80% lysine.; Swine Day, Manhattan, KS, November, 1973
Keywords: Swine day; 1973; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 203; Swine; Lysine; Performance; Finishing barrows; Finishing gilts; Feed efficiency